Pharmacognostic Study of Sangkareho Root (Callicarpa longifolia Lam.) from Pelaihari, South Kalimantan - Fitriyanti Fitriyanti; Yusmalina Yusmalina; Rahmi Muthia (Borneo Journal of Pharmacy, 2020)
Sangkareho (Callicarpa longifolia Lam.) is used traditionally by one of Kalimantan's indigenous tribes, the Dayak Tunjung tribe as a medicine for colds and inflammation, where the plant parts used are the roots. Considering its very potential prospects, research aimed at providing a scientific basis for plant pharmacognostic data needs to be carried out with qualitative methods. The qualitative examination is done by several methods including test identification of organoleptic, macroscopic, microscopic, and chemical compounds. Organoleptic test results showed that the roots have a light brown color, bitter and slightly spicy, and a rather pungent odor. Microscopic test results showed sangkareho root has a length of ± 90 cm; width of ± 1 cm; and for the form of a spear with a ride root system. Microscopic observations are found in the form of epidermal cells, exodermis, cortex, endodermis, bearing files, calcium oxalate crystals, and stone cells. The identification of chemical compounds showed positive results against alkaloids, flavonoids, saponins, and triterpenoids. The thin-layer chromatography profile shows four separate stains with eluent ethyl acetate : methanol : water in a ratio of 8 : 2 : 1, respectively.